Analysis of Serang Culture in Elementary Schools: A Systematic Literature Review (2020–2025) - Suryani, Irma; Wasino, Wasino; Arcindy, Argitha; Armaidi, Indriana Eko (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This study presents the first comprehensive Systematic Literature Review (SLR) on the integration of Serang culture into elementary school education during the 2020–2025 period. Twenty relevant studies were identified from databases such as Google Scholar, ResearchGate, and institutional repositories. The findings indicate that Serang cultural elements—such as debus, rudat, the Serang–Banten dialect, and marhabanan—have been incorporated through local content curricula, extracurricular programs, and thematic learning. These integrations help preserve local wisdom while enhancing students’ character, cultural identity, and literacy in alignment with the Profil Pelajar Pancasila. Successful implementation depends on teacher creativity, community involvement, and government support, supported by digital and contextual learning media like culture-based e-modules and E-LKPD. Nevertheless, challenges persist, including limited standardized materials, uneven teacher competencies, and the absence of long-term evaluation. Overall, this review highlights the potential of Serang culture integration as a sustainable model for strengthening holistic, character-based education in Indonesian elementary schools.